"Minha pele é linguagem" : cena, educação e existência negra no departamento de Artes Cênicas da UFPB. - Silva, Pedro Soares Machado da (2024)
The Performing Arts, Theater and Dance are territories of body work. In this way, the body is the center of these art languages. In this sense, this research seeks to understand how black bodies of students from the Department of Performing Arts (DAC) at the Federal University of Paraíba (UFPB) are violated within their performing and teaching experiences. In order to reach this understanding, the research situates the physical, social and curricular environment of the undergraduate courses in Theater and Dance, in addition to the bachelor's degree course in Theater, which are under the responsibility of the DAC/UFPB. To collect the data, the qualitative focus group methodology was developed, this group being composed of bodies and bodies identified and identified with blackness that make up the student body of the three courses mentioned and having their speeches instigated by a script of questions constructed to understand the experiences through three crossroads: Scene; Education; Existence. In turn, to interpret and analyze the data, Nilma Lino Gomes and Evani Tavares Lima highlight the theoretical framework of the work, the first for dealing with pedagogies for teaching blackness, the second for living and researching Black Scenes. There is still emphasis on escrevivência, a technique used by Conceição Evaristo, responsible here for conducting the poetic translation of the group's speeches, in order to more effectively transmit the unique knowledge of each member's trajectories. Therefore, the research demarcates the existence and, consequently, black resistance in the DAC/UFPB environment and projects the demands of these bodies that ask for and produce Black Scenes and pedagogies.